Initial effects of the COVID-19 pandemic on Ecuadorian Healthcare Providers' self-reported anxiety - Gabriella Gaus Hinojosa (Fundación Salud y Desarrollo Andino, Saludesa Ecuador, 2021)
During the early stages of the COVID-19 pandemic, Ecuador was one of the countries most impacted globally. High instances of corruption, widespread COVID-19 fatalities and cases, and a strained health care system impacted Ecuadorian healthcare providers' occupational responsibilities and environment. The psychological consequences of the COVID-19 pandemic on Ecuadorian healthcare providers are limited. The aim of this study is to evaluate the psychological impact of the COVID-19 Pandemic on Ecuadorian health care providers' anxiety. A nationwide survey of 293 physicians, nurses, and health care workers in Ecuador was conducted to understand their self-reported anxiety as measured by the Zung self-reported anxiety scale. Our findings suggest the overall mean sample score (M = 39.14, SD = 8.17) was just under the clinical anxiety threshold. Additionally, a majority (63%, n = 114) of the sample appeared to meet the clinical threshold for anxiety highlighting the significant psychological toll of the COVID-19 crisis on health care workers. Explanatory factors and future policy and research recommendations are discussed.